Chronic disseminated candidiasis manifesting as hepatosplenic abscesses among patients with hematological malignancies - Chien-Yuan Chen; Aristine Cheng; Feng-Ming Tien; Po-Chu Lee; Hwei-Fang Tien; Wang-Huei Sheng; Yee-Chun Chen (BMC Infectious Diseases, 2019)
Abstract Background The outcomes of deep-seated abscesses attributed to chronic disseminated candidiasis (CDC) in patients with hematological malignancies have rarely been reported in recent years. Methods We retrospectively reviewed and analyzed the data of patients with hematological malignancies who received a diagnosis of CDC at a medical center in Taiwan between 2008 and 2013. Results Sixty-one patients (32 men and 29 women) were diagnosed with CDC. The median age was 51 years (range: 18–83). The overall incidence of CDC was 1.53 per 100 patient-years in patients with hematological malignancies between 2008 and 2013. The highest incidence of CDC was 4.3 per 100 patient-years for acute lymphoblastic leukemia, followed by 3.6 for acute myeloid leukemia. We detected 3 (4.9%) proven, 13 (21.3%) probable, and 45 (73.8%) possible cases of CDC. A total of 13 patients had positive blood cultures for Candida species: C. tropicalis (8), C. albicans (2), C. glabrata (2), and C. famata (1). The median duration of antifungal treatment was 96 days (range: 7–796 days). Serial imaging studies revealed that the resolution rate of CDC was 30.0% at 3 months and 54.3% at 6 months. Five patients (8.2%) had residual lesions that persisted beyond one year. A multivariate analysis of the 90-day outcome revealed that shock was the only independent prognostic factor of 90-day survival in patients with CDC. Conclusion The incidence of CDC did not decrease between 2008 and 2013. Patients with acute leukemia had a higher risk of CDC than those with other hematological malignancies. Imaging studies conducted at 6 months after diagnosis revealed that only half of the patients showed complete resolution. CDC requires prolonged treatment, and serial imaging at 6 months interval is suggested. Shock is the only independent prognostic factor of 90-day survival in patients with CDC.